2022
DOI: 10.1021/acsami.2c00761
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Porous Scaffolds of Hydrogels Modified with TGF-β1 Binding Peptides to Promote In Vivo Cartilage Regeneration and Animal Gait Restoration

Abstract: The treatment of cartilage injury and osteoarthritis has been a classic problem for many years. The idea of in situ tissue regeneration paves a way for osteochondral repair in vivo. Herein, a hydrogel scaffold linked with bioactive peptides that can selectively adsorb transforming growth factor β1 (TGF-β1) was hypothesized to not only afford cell ingrowth space but also induce the endogenous TGF-β1 recruitment for chondrogenesis promotion. In this study, bilayered porous scaffolds with gelatin methacryloyl (Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 67 publications
(106 reference statements)
2
36
0
Order By: Relevance
“…TGF-β1 affinity binding peptides have been also used to produce bilayered porous scaffolds with gelatin methacryloyl hydrogels as a matrix, manufactured via three-dimensional (3D) printing, where the upper layer was covalently bound with TGF-β1 affinity binding peptides that were able to adsorb TGF-β1 and the lower layer was blended with hydroxyapatite for subchondral regeneration. The bilayered scaffolds showed promising therapeutic efficacy, as proven via chondrogenic and osteogenic induction in vitro and osteochondral repair in vivo [45]. In agreement with the previous study, Ju et al developed a new photo-crosslinked gelatin methacryloyl hydrogel (GelMA) modified with a TGF-β1affinity peptide (HSNGLPL), which was able to self-absorb with TGF-β1, and demonstrated that this scaffold was able to promote cartilage repair [46].…”
Section: Transforming Growth Factor-β Mimetic Peptidessupporting
confidence: 57%
“…TGF-β1 affinity binding peptides have been also used to produce bilayered porous scaffolds with gelatin methacryloyl hydrogels as a matrix, manufactured via three-dimensional (3D) printing, where the upper layer was covalently bound with TGF-β1 affinity binding peptides that were able to adsorb TGF-β1 and the lower layer was blended with hydroxyapatite for subchondral regeneration. The bilayered scaffolds showed promising therapeutic efficacy, as proven via chondrogenic and osteogenic induction in vitro and osteochondral repair in vivo [45]. In agreement with the previous study, Ju et al developed a new photo-crosslinked gelatin methacryloyl hydrogel (GelMA) modified with a TGF-β1affinity peptide (HSNGLPL), which was able to self-absorb with TGF-β1, and demonstrated that this scaffold was able to promote cartilage repair [46].…”
Section: Transforming Growth Factor-β Mimetic Peptidessupporting
confidence: 57%
“…Adapted with permission from Ref. [ 76 ]. B. Bilayered scaffold with BL and CL separated by a thin electrospun PCL tidemark.…”
Section: Biomimetic Architectures In Mzsmentioning
confidence: 99%
“…While monophasic scaffolds have failed to simultaneously combine chondrogenicity and osteogenicity [ 67 ], recently developed bilayered scaffolds tend to address this issue. A common strategy for the design of bilayered scaffolds with both chondrogenicity and osteogenicity is to use polymers as the cartilage layer and polymer-embedded bioceramics as the bone layer [ 21 , 57 , 59 , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. Studies reported bilayered scaffolds coupling polymer-camphene [ 78 ], two different polymers [ 68 ], polymer-bioglass [ 79 ], and decellularized cartilage matrix-decalcified bone matrix [ 66 , 80 ] to promote both osteogenesis and chondrogenesis.…”
Section: Biomimetic Architectures In Mzsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell–material interactions are particularly important in the fields of biomaterials, cell biology, , and regenerative medicine. Since various functional systems of organs and bodies are composed of multiple types of cells, strategies to regulate the migration of cells in a selective way need to be developed. For instance, in the treatment of acute periodontitis, the operation processes involve the regulation of the multitype cells, including the gingival connective tissue cells, epithelial cells, periodontal ligament cells, bone cells, etc . In particular, after implanting a stent to deal with cardiovascular diseases, endothelial cells (ECs) are expected to migrate faster than smooth muscle cells (SMCs) on the biomaterial surface.…”
Section: Introductionmentioning
confidence: 99%